ANALISIS LIKUIDITAS, PROFITABILITAS, DAN LEVERAGE SERTA PENGARUHNYA TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG BERADA PADA INDEX LQ45 DI BURSA EFEK INDONESIA (BEI) PERIODE 2013-2015 - Nadiya Nidaul Khairiyah; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2017)
This research is conducted with the aim of: 1) to know and analyze the influence of liquidity, profitability and leverage simultaneously to stock prices at companies that are in the index lq45 period 2013-2015 listed on the indonesia stock exchange. 2) to know and analyze the effect of liquidity, profitability and leverage partially to share price at company which is in index lq45 period 2013-2015 which listed in Indonesia Stock Exchange. The population used in this study are all companies listed on the Indonesia Stock Exchange in 2013-2015. Sample selection using purposive sampling. Based on the criteria, obtained 30 companies are samples in this study. The method used in this study using multiple linear regression method. Based on the results of the analysis can be put forward several conclusions as follows: 1) f test results show that the simultaneous current ratio, return on asset, and debt to equity ratio significant effect on stock prices. This is shown by the significance value of f <0.05 which is 0.000. 2) the result of t test shows the variable of current ratio has significant negative effect to stock price. This is indicated by the significance value <0.05 that is equal to 0.001. 3) variable return on asset has a significant positive effect on stock prices. This is indicated by the significance value <0.05 is 0.000. 4) debt to equity variable has no significant effect on stock price. This is indicated by the significance value> 0,05 that is equal to 0,667.